2012
DOI: 10.1016/j.jcis.2012.03.038
|View full text |Cite
|
Sign up to set email alerts
|

Surface-associated metal catalyst enhances the sorption of perfluorooctanoic acid to multi-walled carbon nanotubes

Abstract: Surface-associated metal catalyst enhances the sorption of perfluorooctanoic acid to multi-walled carbon nanotubes Journal of Colloid and Interface Science, 377, 342-346, 2012 2 AbstractPerfluorooctanoic acid (PFOA) sorption behaviour of two commercial multi-walled carbon nanotubes (MWCNTs) (C 150 P from Bayer MaterialScience: BA and C-MWNTs from NanoTechLabs Inc.: CP) was investigated from aqueous solution. The BA nanotubes contain Co/Mn/Mg/Al catalysts both on their outer surface and in the inner bore whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 59 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…Carbon nanotubes (CNTs) consist of rolled-up graphene sheets (Iijima, 1991) that have been used in many commercial applications such as electrical cables and wires (Janas et al, 2014), hydrogen storage (Dillon et al, 1997), solar cells (Guldi et al, 2005), radar absorption (Lin et al, 2008), and may potentially be employed in environmental remediation (Mauter and Elimelech, 2008;Pan and Xing, 2012) and water treatment (Camilli et al, 2014;Li et al, 2012;Zhang et al, 2010). The widespread use of CNTs will undoubtedly result in their release into the environment (Gottschalk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon nanotubes (CNTs) consist of rolled-up graphene sheets (Iijima, 1991) that have been used in many commercial applications such as electrical cables and wires (Janas et al, 2014), hydrogen storage (Dillon et al, 1997), solar cells (Guldi et al, 2005), radar absorption (Lin et al, 2008), and may potentially be employed in environmental remediation (Mauter and Elimelech, 2008;Pan and Xing, 2012) and water treatment (Camilli et al, 2014;Li et al, 2012;Zhang et al, 2010). The widespread use of CNTs will undoubtedly result in their release into the environment (Gottschalk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research with CNTs and surfactants focused on determination of breakthrough curves (BTCs), but did not measure the influence of surfactants on CNT retention profiles (RPs) (Lu et al, 2013;Lu et al, 2014). Liang et al (2013) demonstrated that the presence of surfactants had a large influence on the shape of the RPs for silver nanoparticles in quartz sand, but little influence on their BTCs. This was attributed to competitive blocking (e.g., filling) of silver nanoparticle retention sites by surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…They have been utilized in numerous commercial applications (Gohardani et al, 2014) such as electrical cables and wires (Janas et al, 2014), solar cells (Guldi et al, 2005), hydrogen storage (Jones and Bekkedahl, 1997), radar absorption (Lin et al, 2008) and considering as absorbents for environmental remediation and water treatment (Camilli et al, 2014;Li et al, 2012;Mauter and Elimelech, 2008;Pan and Xing, 2012;Zhang et al, 2010) due to their unique electric, chemical, and physical properties. The widespread commercial and potential environmental applications will undoubtedly result in their release into the subsurface.…”
Section: Introductionmentioning
confidence: 99%
“…These suspensions were dispersed by ultrasonicating the stock suspension for 15 min at 65 W, and then repeating this process 10 min before injection into soil columns. This low energy of sonication does not damage the MWCNTs (Li et al, 2012).…”
mentioning
confidence: 95%
“…Because of their high chemical stability, PFAAs have not been shown to be effectively degraded using biological or chemical treatment technologies, and thus physical sorption is the primary option currently available for their removal from water. Activated carbon (AC) has a long history in environmental applications as a sorbent for purifying drinking water and wastewater (Karanfil and Kilduff, 2000;Li et al, 2002), including for PFAAs removal (Yu et al, 2009;Li et al, 2012). AC exhibits superior adsorptive capacity for organic pollutants in aqueous solution because of its porous structure, large surface area and diverse surface chemistry (Rozwadowski et al, 1979;Qu et al, 2009).…”
Section: Introductionmentioning
confidence: 99%